Seismic Site Response Study in Greater Tezpur City, Assam, Ne India - Nandita Dutta; Barsha Das (Current Advances in Geography, Environment and Earth Sciences Vol. 7, 2022)
The North East India falls in zone V according to the seismic zonation map of India (BIS, 2002). The frequency of occurrence of moderate and large magnitude earthquakes is significantly high throughout the region. The major tectonic blocks constituting the NE India are the Assam-Arakan Folded Belts, the Arunachal Himalayas, the Mishmi Massif, the Shillong – Mikir plateau and the North – South Fold Belts of Tripura and the adjacent Bengal Alluvial Basin. Most of the events falling in the tectonic domains of the eastern Himalayas including Mishmi massif, Naga Hills, Shillong-Mikir Plateau, Surma basin and adjacent Bengal Alluvial Plains are of crustal origin (h<70km) except for a few events in the N-W trending wedge shaped block lying between the Kopili and Bomdila faults. Seismic site factor or site amplification measurement has been recognized as the most accepted tool in seismic hazard assessment and risk evaluation taking into account the source and site conditions considering all probable hazards mapped in a much larger scale. Therefore, seismic site response study and preparation of seismic microzonation maps for highly populated urban areas of NE India is considered as a measure of site-specific hazard estimation. Tezpur is the administrative headquarter of Sonitpur district and it is an up growing city. The urban Tezpur lies to the northern extremity of the seismically active Mikir Plateau, and bounded by a complex tectonic regime. It is bordered with MBT to the north, Mikir Hills to the south – southeast, Assam valley to the ENE and Kopili lineament to the west characterized by intense intra plate seismic activity.